THE EFFECT OF USING CLUSTERING TECHNIQUE IN STUDENTSâ WRITING SKILL OF DESCRIPTIVE TEXT AT THE FIRST GRADE SMPN 2 RAMBAH HILIR - Herlambang, Gusti; Sukma, Dian; -, Eripuddin (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The studentsâ writing skill of descriptive text at the first grade SMPN 2 Rambah Hilir was low because they do not know how to write a good descriptive text and lack of time to practice. The findings shows that there is any significant effect between teaching descriptive text with using clustering technique. It can be seen of the value of t0(tvalue) = 6,442 is bigger than tt(ttable) with significance 5%= 2,00 by using t-test. It can be concluded that there is any significance effect between teaching descriptive text by using clusteringtechnique.